2002
DOI: 10.2308/accr.2002.77.s-1.139
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Financial Reporting Quality: The Effects of Financial Expertise vs. Financial Literacy

Abstract: Audit committees evaluate financial reporting quality as part of their corporate oversight responsibilities. Given this responsibility, the national stock exchanges now require all audit committee members to be financially literate and at least one member to have financial expertise. In light of recent debates over this requirement, we provide evidence on how experts and literates differ in their evaluations of financial reporting quality. Results suggest that experts' evaluations of financial reporting qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(195 citation statements)
references
References 22 publications
7
150
0
11
Order By: Relevance
“…In this spirit, the research of Bodnaruk and Simonov (2015) is an interesting example for simultaneously analyzing individuals' financial behavior in the private and in the professional domain. To us, it appears that financial literacy in the business context is an interesting and still largely under-researched subject: as can be inferred from Table 1, 19 out of the 20 most cited papers focus on financial decisions of households, the only exception being McDaniel et al (2002), who discuss financial literacy in the context of audit committees.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…In this spirit, the research of Bodnaruk and Simonov (2015) is an interesting example for simultaneously analyzing individuals' financial behavior in the private and in the professional domain. To us, it appears that financial literacy in the business context is an interesting and still largely under-researched subject: as can be inferred from Table 1, 19 out of the 20 most cited papers focus on financial decisions of households, the only exception being McDaniel et al (2002), who discuss financial literacy in the context of audit committees.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Several studies argue that audit committee members' knowledge or experience is directly associated with the committee's effectiveness (McDaniel et al 2002;Bedard et al 2004). For example, Jun Lin et al (2008) argue that the audit committee's main task is to supervise corporate financial reporting and auditing processes, therefore, its members should have the capability to understand the issues being examined or discussed.…”
Section: Members' Experiencementioning
confidence: 99%
“…The existence of audit committee can be seen as a mechanism for reducing information asymmetry between managers and owners and also for protecting investors (McMullen, 1996;McDaniel et al, 2002). Klein (2002) indicated that the existence of independent audit committee tends to reduce the possibility of earnings management, thus improving transparency.…”
Section: Audit Committeementioning
confidence: 99%